KESIAPAN PESERTA DIDIK KELAS VIII UNTUK MENGHADAPI UJIAN SEMESTER DI SMP NEGERI 17 PADANG - Haris, M.; Arief, Asmaiwaty; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Based on the observations of research Practical Experience Filed Tuition and Counseling School at SMP Negeri 17 Padang, especially when researchers overseen activities semester exams, it is clear that there are students not ready physically, mentally and not ready to discipline for the exam looks less good. The aimed his study to describe: How readiness physical, mentally and discipline of students to the class VIII to confront the semester exam at SMP Negeri 17 Padang. This research is a descriptive qualitative to got obtaining information in the form of a statement, explaining, words, picture of language. Source of the data is students of the class VIII at SMP Negeri 17 Padang. Total data source is 238 students. In this research Simple Random Sampling done by lottery or lottere was applied. Total of sources research the data 70 students. Research instruments such as questionnaires and interviews, used the technique analysis percentage of engineering analysis interviews. Results of this research said that: (1) Readiness physical to the students for the exam criteria very good is 64.29%. (2) the readiness mentally of the students for the exam the criteria very good is 51.43%. (3) The discipline of students in the exam, including the criteria that is either 55.71%, to addition information from the interview to headmaster and three people guardian class any students not discipline to exam, especially in the discipline of time students still have exams coming late. Based on the found of the research, so the students to recommended the exam and comply with maintaining readiness criteria very well, to headmaster, guardian class and teacher counselor for more attention to discipline students for exams.